Photocarrier-induced band-gap renormalization and ultrafast charge dynamics in black phosphorus. (9th April 2019) - Roth, S; Crepaldi, A; Puppin, M; Gatti, G; Bugini, D; Grimaldi, I; Barrilot, T R; Arrell, C A; Frassetto, F; Poletto, L; Chergui, M; Marini, A; et al.
Abstract: With its tunable band-gap and its unique optical and electronic properties black phosphorus (BP) opens exciting opportunities for optoelectronic nanotechnology. The band-gap extends from the visible to the mid-infrared spectral range, as a function of sample thickness and external parameters such as electric field and pressure. This, combined with the saturable absorption and in-plane anisotropic optical properties, makes BP a versatile platform for realizing polarization-sensitive photodetectors and absorbers. Although its near-equilibrium properties have been intensively studied, the development of efficient ultrafast optical devices requires detailed knowledge of the temporal dynamics of the photoexcited hot-carriers. Here we address the electronic response of BP to an ultrafast laser excitation, by means of time-and angle-resolved photoelectron spectroscopy. Following the optical excitation, we directly observe a shift of the valence band (VB) position, indicative of band-gap renormalization (BGR). Our data also show that the hole population in the VB relaxes with a characteristic time ps, while the lifetime of the electrons accumulated at the minimum of the conduction band is ps. The experimental results are well reproduced by ab initio calculations of the out-of-equilibrium electronic properties. Our study sets the reference for the ultrafast carrier dynamics in BP and demonstrates the material's ultrafast BGR, which is promising for optoelectronic switches.